PENGARUH KEPEMIMPINAN, KOMPETENSI TERHADAP KEPUASAN KERJA DAN KINERJA APARATUR SIPIL NEGARA PADA DINAS KEBUDAYAAN DAN KEPARIWISATAAN PROVINSI SULAWESI SELATAN - Agustinus Ruti; Andi Mappatompo (COMPETITIVENESS, 2018)
This study aims to find out and analyze the Influence of Leadership, Competence on Job Satisfaction and Performance of State Civil Apparatus in the Department of Culture and Tourism of South Sulawesi Province. As well as knowing and analyzing the dominant variables affecting the performance of the Department of Culture and Tourism of South Sulawesi Province. The research has been conducted at the Office of Culture and Tourism of South Sulawesi Province with a period of implementation for 1 month, namely the month of March to April 2018 with a sample of 59 people. The analysis method used in this research is descriptive statistical method and path analysis. The results showed that: Leadership has a significant influence on job satisfaction with a value of p = 0.004 0.05 with a coefficient value of 0.322, Competency has a significant influence on job satisfaction with p = 0.000 0.05 with a coefficient value of 0.499, Leadership has a significant influence on employee performance with p = 0.002 0.05 with a coefficient value of 0.405, Competency has an insignificant positive influence on job satisfaction with p = 0.425 0.05 with a coefficient value of 0.115, Job satisfaction has a significant influence on performance with p = 0.021 0.050 with a coefficient value of 0.233, furthermore Leadership has a significant influence on performance through job satisfaction with a coefficient value of 0.075, this coefficient shows that good leadership in the Office of Culture and Tourism of South Sulawesi Province can increase employee job satisfaction so that it has an impact on improving employee performance. And Competency has a significant influence on employee performance through job satisfaction with a coefficient value of 0.116, this coefficient shows that the more appropriate competencies that employees have with their work will increase job satisfaction and ultimately impact on the performance of employees who are getting better. Keywords: Leadership, competence, job satisfaction and performance